2017
DOI: 10.1097/pec.0000000000001311
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Causes of Bruises in Premobile Infants

Abstract: Objective This study had 2 objectives. First, to determine the behavior of physicians evaluating premobile infants with bruises. Second, and most importantly, to learn whether infants with unexplained bruising who had been initially evaluated by primary care and emergency department (ED) physicians are as likely to have their bruises attributed to child abuse as those children evaluated by child abuse physicians. Methods Primary care, ED, and child abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…It is important for clinicians to be educated in recognizing the sometimes subtle signs of non-accidental injuries such as bruising or fractures in non-cruising infants, vomiting without diarrhea, lethargy, poor oral intake, or injuries without adequate trauma history (114,115). Studies have demonstrated frequently missed opportunities to diagnose sentinel abusive injuries in children who were later diagnosed with AHT (116)(117)(118). Unfortunately, as shown in a recent study by Letson et al there has not been a significant improvement in the rate of missed sentinel abuse events over the last two decades (117).…”
Section: Preventionmentioning
confidence: 99%
“…It is important for clinicians to be educated in recognizing the sometimes subtle signs of non-accidental injuries such as bruising or fractures in non-cruising infants, vomiting without diarrhea, lethargy, poor oral intake, or injuries without adequate trauma history (114,115). Studies have demonstrated frequently missed opportunities to diagnose sentinel abusive injuries in children who were later diagnosed with AHT (116)(117)(118). Unfortunately, as shown in a recent study by Letson et al there has not been a significant improvement in the rate of missed sentinel abuse events over the last two decades (117).…”
Section: Preventionmentioning
confidence: 99%
“…[7][8][9][10] Published evidence confirms that measurable differences exist between bruising from nonabusive and abusive injury in infants and young children. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] An evidence-based screening tool may prevent these high-stakes failures.…”
Section: Introductionmentioning
confidence: 99%
“…32,46,47 This reluctance to consider abuse when a young child presents with injury is especially relevant in the field of child abuse, where a seemingly minor and self-resolving injury, such as a single bruise in a premobile infant, should trigger concern for abuse. [48][49][50] While linking CED providers to a regional CPT when infants present with high-risk injuries, such as bruising, has the potential to help overcome some of these barriers, we similarly found that CED providers wished for their own discretion about when to seek a consultation from the CPT and often felt that they were able to discern independently between abusive and nonabusive injury although available research does not support this view. 3,23,51,52 In contrast, when ED providers consulted the CPT, they appreciated the screening questions asked by the CPT to help determine the need for further evaluation, especially in settings with limited social work availability.…”
Section: Primary Outcomementioning
confidence: 82%
“…These include difficulty distinguishing abusive from nonabusive injury, socioeconomic and racial biases that falsely allow providers to feel capable of discerning which caregivers would and would not abuse their children, concerns about the effectiveness of CPS, and fear of falsely “accusing” caregivers of abusing their children 32,46,47 . This reluctance to consider abuse when a young child presents with injury is especially relevant in the field of child abuse, where a seemingly minor and self‐resolving injury, such as a single bruise in a premobile infant, should trigger concern for abuse 48–50 . While linking CED providers to a regional CPT when infants present with high‐risk injuries, such as bruising, has the potential to help overcome some of these barriers, we similarly found that CED providers wished for their own discretion about when to seek a consultation from the CPT and often felt that they were able to discern independently between abusive and nonabusive injury although available research does not support this view 3,23,51,52 .…”
Section: Discussionmentioning
confidence: 99%